Linear IgA disease/Dowling-Meara epidermolysis bullosa simplex. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Today linear IgA disease is the least rare autoimmune bullous disease in children; Dowling-Meara epidermolysis bullosa simplex (DMEBS) is a rare autosomal dominant disease. Despite the different pathogenesis the two diseases may occur in the child from the first months of life with similar annular or arcuate bullous lesions and therefore require a differential diagnosis.